2020
DOI: 10.1002/agg2.20110
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between water use efficiency and light use efficiency in four row crop canopies

Abstract: Quantitative evidence of light use efficiency (LUE) controls on water use efficiency (WUE) is lacking, especially comparatively across row crops. Field research experiments (2016-2018) were set up for maize (Zea mays L.), soybean [Glycine max (L.) Merr.], sorghum [Sorghum bicolor (L.) Moench], and winter wheat (Triticum aestivum L.), under optimal growth conditions in dry sub-humid conditions. Overall, LUE was able to explain 52% of variance in WUE, and were related as WUE = 1.73 LUE, although crop-specific va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Higher LUE could lead to an increase of GPP , which would relieve carbon starvation and facilitate water transport. The R 2 between WUE and GPP was higher in drylands than in fields (Kukal & Irmak, 2020), and the R 2 between LUE and WUE increased when water stress was high. Drought thus seemed to enhance the correlation between LUE and WUE .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher LUE could lead to an increase of GPP , which would relieve carbon starvation and facilitate water transport. The R 2 between WUE and GPP was higher in drylands than in fields (Kukal & Irmak, 2020), and the R 2 between LUE and WUE increased when water stress was high. Drought thus seemed to enhance the correlation between LUE and WUE .…”
Section: Discussionmentioning
confidence: 99%
“…The variation of r indicated that the relationship would enhance with increasing water stress (Huang et al, 2017). The relationship between LUE and WUE of irrigated crops is controlled by VPD (Kukal & Irmak, 2020). However, VPD also significantly affects LUE of irrigated crops, particularly under moist conditions (Yuan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High WUE was proved to be related to low RUE under probable drought (Dercas and Liakatas, 2006). In contrast, WUE and RUE are directly proportional under optimal growth conditions (Ullah et al, 2019;Kukal and Irmak, 2020). However, little is known about the interrelationships of radiation and water use processes at both leaf and canopy levels in agricultural ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the connection between WUE and RUE response to progressive soil drying at different growth stages remains unclear. WUE and RUE are inversely related to canopy conductance (gc) (Sadras et al, 1991;Hernández et al, 2021), which may be suitable to distinguish and communicate the WUE and RUE relations (Kukal and Irmak, 2020). In addition, changes in canopy structure [e.g., leaf angle, plant height, leaf area index (LAI)] reflect both in light transmittance, and reflectance under water stress conditions (Holmes and Keiller, 2002;Onoda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%